Fractal features of soil grain-size distribution in a typical Tamarix cones in the Taklimakan Desert, China - Zhengwu Dong; Donglei Mao; Mao Ye; Shengyu Li; Xiaodong Ma; Suiyunhao Liu (Scientific Reports, 2022)
Abstract Tamarix cones play key roles in preventing sand erosion and maintaining regional ecosystem stability. This study aimed to explore the characteristics of soil grain size distribution (GSD) in Tamarix cones across the Taklimakan Desert, verify the relationships between soil grain composition and the fractal dimension, and analyze the relationships between soil GSD and environmental factors. Soils of the Tamarix cones from 0 to 500 cm soil depth were sampled every 20 cm at four sites (Qiemo, Qira, Aral, and Tazhong) along the periphery to the hinterland of the Taklimakan Desert. A total of 300 soil samples were collected to measure soil grain sizes and soil properties. Soil grain size composition was dominated by silt and very fine sand, and the fraction of fine particles decreased and that of the coarse particles increased with soil depth, except for at Tazhong. This suggested that suspension-size particles are the main component of the soil GSD and decrease with the increasing depth in the profiles at the Tamarix cones. The soils were poorly and moderately poorly sorted. Kurtosis generally showed a mesokurtic peak, and the GSD was negatively skewed towards the coarser particles. The fractal dimensions of GSD decreased in the following order Qiemo (2.30) > Qira (2.07) > Aral (1.99) > Tazhong (1.96) because of the increase of coarse particles. The fractal dimension had a strong positive correlation with the clay and silt fractions, and a strong negative correlation with the sand fraction, indicating that the fractal dimension can reflect the characteristics of the soil GSD. The strong relationships between the fractal dimensions and selected soil properties indicate that the fractal dimension can not only quantify changes in soil properties, but also reflect the degree of desertification and degradation in the desert region. Considering the strong wind activities and different deposition sources in the Taklimakan Desert, this study provides a deep insight into the soil formation processes of Tamarix cones within extreme arid desert ecosystems.